2019
DOI: 10.1177/0883073819877334
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Outcomes of Pediatric Monophasic and Recurrent Idiopathic Optic Neuritis

Abstract: Limited data exist on isolated optic neuritis in children. We report the clinical features and treatment of pediatric subjects with monophasic and recurrent idiopathic optic neuritis. This retrospective cohort study of patients with isolated optic neuritis identified 10 monophasic and 7 recurrent optic neuritis cases. Monophasic optic neuritis patients were older (mean 13.3 ± 4.22) than those with recurrent idiopathic optic neuritis (9.86 ± 3.63). Females represented 50% of monophasic and 85.7% of recurrent id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
3
0
2
Order By: Relevance
“…Limited data exist on pediatric-onset optic neuritis. The incidence of optic neuritis in children is estimated around 1-5 per 100.000 per year ( Jonzzon et al., 2020 ). To confirm the diagnosis, serum detection for antibodies against AQP4-IgG and MOG-IgG should be done.…”
Section: Discussionmentioning
confidence: 99%
“…Limited data exist on pediatric-onset optic neuritis. The incidence of optic neuritis in children is estimated around 1-5 per 100.000 per year ( Jonzzon et al., 2020 ). To confirm the diagnosis, serum detection for antibodies against AQP4-IgG and MOG-IgG should be done.…”
Section: Discussionmentioning
confidence: 99%
“…Although the histopathology of cerebral lesions in MOGAD patients demonstrates relative preservation of axonal structures, severe visual impairment or functional blindness have been reported in >30% of MOGAD adults ON patients, and OCT studies repeatedly demonstrated profound axonal degeneration with loss of retinal ganglion cells [ 11 14 ]. Although MOG-IgG antibodies have been frequently reported in children with ON, there are only a few studies investigating retinal changes and visual outcomes in this population [ 5 , 15 17 ]. Moreover, there are no studies comparing ON course and outcome in children and adults with MOGAD.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to be able to correct the manifestations of the ischemic process and trophic disorders in time. The pathophysiology and natural course of idiopathic optic neuritis are insufficiently studied [10]. The chronic ischemia leads to diffuse death of axons [11].…”
mentioning
confidence: 99%